2019
DOI: 10.1097/scs.0000000000005038
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Distraction Osteogenesis and Single-Stage Remodeling for Correction of Unilateral Coronal Craniosynostosis

Abstract: Background: Unilateral coronal craniosynostosis is a challenging condition in craniofacial surgery. Frontoorbital advancement by single-stage resorbable remodeling and distraction osteogenesis (DO) techniques have known intraoperative differences, but their comparative outcomes are less well characterized. Methods: A systematic literature search of the MEDLINE, EMBASE, LILACS, and Web of Science databases was conducted. The search was performed using te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Previous literature comparing these 2 techniques in patients with unicoronal craniosynostosis showed similar results, with a low risk of unplanned reoperation 15 and a higher incidence of dural tear in the OCVR cohort compared with the DO cohort. 13…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature comparing these 2 techniques in patients with unicoronal craniosynostosis showed similar results, with a low risk of unplanned reoperation 15 and a higher incidence of dural tear in the OCVR cohort compared with the DO cohort. 13…”
Section: Discussionmentioning
confidence: 99%
“…4 Many techniques have been described for the treatment of patients with ULS, such as endoscopic suturectomy, distraction osteogenesis (DO), open posterior calvarial reconstruction, and bone-flap remodeling or switching. [1][2][3][4][5][6][7][8][9][10][11][12][13] At the time of this writing, the most common treatment for ULS was open posterior cranial vault remodeling (OCVR), however, reports on the effectiveness of this technique for treating this condition have been mixed. Zoller et al 12 indicated that OCVR resulted in the normalization of intracranial pressure and produced consistently favorable esthetic outcomes in patients with ULS.…”
mentioning
confidence: 99%
“…18 However, they noticed that there was no significant difference between the 2 surgical modalities. 17 However, because their analysis included both 1-piece and 2-piece FODO, the difference between FODO and FOAR was reduced. Consequently, further long-term research on 1-piece FODO is needed to clarify the advantages of FODO over FOAR.…”
Section: Discussionmentioning
confidence: 99%
“…Corkum et al 17 conducted a systematic literature review including 223 FOAR and 69 FODO in patients with unilateral coronal synostosis 18 . However, they noticed that there was no significant difference between the 2 surgical modalities 17 . However, because their analysis included both 1-piece and 2-piece FODO, the difference between FODO and FOAR was reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation